p21 protects cardiomyocytes against ischemia-reperfusion injury by inhibiting oxidative stress - Li, Hong; Zou, Tong; Meng, Shuai; Peng, Yun‑Zhu; Yang, Jie‑Fu (Molecular medicine reports, 2018)
Ischemic heart disease is a major health threat, resulting in a large number of mortalities annually worldwide. Oxidative stress is one of the main causes of cell death during ischemia‑reperfusion (IR) injury. Cyclin dependent kinase inhibitor 1A (known as p21) is important in protecting tissues against IR injury, however the mechanism remains unknown. In the present study, oxygen‑glucose deprivation and subsequent reoxygenation (OGD/R) in H9c2 heart‑derived myocytes was used as a model to study myocardial IR injury in vitro. mRNA and protein expression levels were determined by reverse transcription‑quantitative polymerase chain reaction and western blotting, respectively. The levels of reactive oxygen species were measured using the fluorescence dye 2',7'‑dichlorodihydrofluorescein diacetate. The present data demonstrated that p21 expression was upregulated by tumor protein p53 (p53) in H9c2 cells exposed to OGD/R. p21 protected H9c2 cells against OGD/R‑induced oxidative stress. In addition, p21 mediated upregulation of NF‑E2‑related factor‑2 (Nrf2), a regulator of antioxidant responses, which in turn suppressed cell death in H9c2 cells subjected to OGD/R. Thus, activation of the p53/p21/Nrf2 signaling pathway may be an important adaptive response that limits oxidative injury during IR.